2013
DOI: 10.1021/mp400513k
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modeling of the in Vitro Hepatic Disposition of Mycophenolic Acid and Its Glucuronide in Sandwich-Cultured Human Hepatocytes

Abstract: In recent years, it has become increasingly important to test the safety of circulating metabolites of novel drugs as part of drug discovery and development programs. Accordingly, it is essential to develop suitable methods for identifying the major metabolites and their disposition in animal species and in humans. Mycophenolic acid (MPA), a selective inosine-5'-monophosphate dehydrogenase (IMPDH) inhibitor, is metabolized by glucuronidation and enterohepatic circulation of MPA-glucuronides is an important fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 51 publications
1
28
0
Order By: Relevance
“…Recently, Pfeifer et al (2013a,b) and Matsunaga et al (2014) demonstrated the importance of the interplay between basolateral and canalicular efflux in the systemic and hepatic disposition of rosuvastatin and mycophenolic acid glucuronide, respectively. Extensive biliary excretion of rosuvastatin and mycophenolic acid glucuronide required mathematical modeling to deconvolute the contribution of basolateral versus canalicular transport.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Pfeifer et al (2013a,b) and Matsunaga et al (2014) demonstrated the importance of the interplay between basolateral and canalicular efflux in the systemic and hepatic disposition of rosuvastatin and mycophenolic acid glucuronide, respectively. Extensive biliary excretion of rosuvastatin and mycophenolic acid glucuronide required mathematical modeling to deconvolute the contribution of basolateral versus canalicular transport.…”
Section: Discussionmentioning
confidence: 99%
“…Cryopreserved human hepatocytes were thawed, plated, and cultured as described in our previous study (Matsunaga et al, 2014), and human SCHs on day 4 were used. Modulation of Ca 2+ in the incubation buffer was applied to maintain or disrupt the canalicular networks between cells sealed by tight junctions.…”
Section: Methodsmentioning
confidence: 99%
“…Using this approach, the masses of compounds in the bile canalicular lumen can be measured with Ca 2+ -containing and Ca 2+ -free buffers (B-CLEAR technology; Qualyst Transporter Solutions, Durham, NC) (Brouwer et al, 2013). Metabolism and hepatobiliary transport studies of human SCHs were performed as described in our previous report (Matsunaga et al, 2014). In brief, human SCHs were incubated with Ca 2+ -containing or Ca 2+ -free buffer containing bosentan at an initial concentration of 1 mM at 37°C for 3, 5, 10, 15, 20, 30, or 45 minutes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this limitation, mechanistic pharmacokinetic modeling coupled with data from sandwichcultured hepatocytes has been used to deconvolute the relative contribution of various clearance (CL) pathways to the disposition of rosuvastatin, mycophenolic acid, and 3 H-taurocholic acid (TCA) (Pfeifer et al, 2013c;Matsunaga et al, 2014;Yang et al, 2015). Transporters are expressed and properly localized in the sandwich-cultured hepatocyte system, which can be used to assess the function of multiple transporters (Yang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%